COLLABORATIVE DECISION-MAKING ON THE INBOUND AND OUTBOUND AIR TRAFFIC FLOW IN AIR TRAFFIC MANAGEMENT - A. V. Lugovaya; A. E. Konovalov (Научный вестник МГТУ ГА, 2017)
The article introduces the general solution – to regulate air traffic flow through the implementation of a set of operational procedures and automated processes for tactical airspace planning and collaborative decision-making (AMAN, DMAN, CDM, A-CDM).The specific solution – to unite all airport operators in gross productivity is suggested. It gives them a single image of the air and ground space and the decision-making effectiveness.The acceptance rate of loaded aerodromes depends on the ability of ATS units at these aerodromes providing approach, arrival and departure for the required airspace capacity of the aerodrome area.The basis of module is a manual procedure, in which the air traffic controller arranges departures or arrivals in real time. Furthermore, there are problems that lead to sub-optimal control decisions especially in taxi procedures planning for departure and holding arrival/departure.According to the experience of airports workload in Europe, the optimal decision-making is successful implementation of new operational procedures and automated processes for tactical airspace planning and collaborative decisionmaking (AMAN, DMAN, CDM, A-CDM).Arrival Manager (AMANs) systems are primarily designed to provide automated sequencing support for the ATCOs handling traffic arriving at an airport, continuously calculating arrival sequences and times for flights, taking into account the locally defined landing rate, the required spacing for flights arriving to the runway. AMAN system can be an integral part of the A-CDM process for interested operators. Departure Manager (DMAN) is a planning system to improve departure flows at airports.Nowadays, the information on airport operations and aircraft readiness is used partly when ATMF is planning the traffic flow throughout the entire ATM system. The most important decision is the information exchange between the interested operators who are criticized for achieving performance indicators for the busiest airports.Airport Collaborative Decision Making (A-CDM) and Collaborative Decision Making (CDM) both contribute to solve all these problems.